Silica-coated magnesium ferrite nanoadsorbent for selective removal of methylene blue - Supawitch Hoijang (2020)
© 2020 Elsevier B.V. This paper demonstrates the adsorption capability of silica-coated magnesium ferrite nanoparticles (MgFe2O4@SiO2 NPs) for the selective adsorption of methylene blue (MB). The MgFe2O4@SiO2 NPs were generated from MgFe2O4 NPs by coating with a thin silica shell. After fully characterizing the MgFe2O4@SiO2 NPs, selective adsorption studies were carefully investigated by using three types of representative dyes: cationic (MB, rhodamine B, and malachite green), anionic (methyl orange and Congo red), and neutral (neutral red) dyes. Efficient removal of MB by the MgFe2O4@SiO2 adsorbents was observed for both individual and mixed dye systems, demonstrating excellent selectivity for MB. To optimize the adsorption capacity for MB removal, several parameters (i.e., initial solution pH, initial dye concentration, and contact time) were carefully investigated. In all cases, the magnetoresponsive adsorbents were easily separated from the solution by using an external magnet. Regeneration of the MgFe2O4@SiO2 NPs for MB removal was also performed to investigate the stability and reusability of the adsorbent. The recycling tests revealed that the MB removal efficiencies remained high after ten adsorption-desorption cycles. On the whole, the MgFe2O4@SiO2 NPs were found to be efficient, selective, and reusable adsorbents for MB removal.